A hydrochemistry and multi-isotopic study of groundwater origin and hydrochemical evolution in the middle reaches of the Kuye River basin. (November 2018) - Fu, Changchang; Li, Xiangquan; Ma, Jianfei; Liu, Lingxia; Gao, Ming; Bai, Zhanxue
Abstract: The Kuye River basin lays in an economically and ecologically important area, therefore, the groundwater quality issues are of growing concern in this semi-arid region. In the present study, the combination of techniques (i.e. piper diagram, ionic ratios, Gibbs diagrams, multiple isotopic analyses etc.) provided an efficient way for analyzing the groundwater origin and hydrochemical processes that affected water chemistry. The groundwater type was CaHCO3 in low TDS values and NaCl/SO4 in high TDS values in both shallow unconfined and deep Cretaceous-Jurassic semi-confined aquifer. And, furthermore, Na +, Cl −, SO4 2− and F − were the dominated parameters deteriorating the groundwater quality. In general, groundwater was of meteoric origin and the more depleted δ 18 O and δD features of CJY groundwater samples indicated that the groundwater was formed during the wetter and colder climate. The rock weathering in conjunction with the cation exchange absolutely predominated in geochemical evolution and deuterium excess method quantified that mineral dissolution contributed most of the salinity (67–92%) of the groundwater. The SO4 2− of the groundwater was primary from the dissolution of sulfate minerals, next was the atmospheric precipitation. In addition, bacterial sulfate reduction was an important reaction affecting the SO4 2− concentration in the groundwater from CJY aquifer. The hydrochemical type of high fluoride groundwater in the study area was NaHCO3 or NaCl/SO4 and it was mainly from the dissolution of fluoride bearing minerals. NaHCO3 water was favorable for F − enrichment due to CaF2 solubility and NaCl/SO4 type water may favor the F − enrichment by lower its activity in groundwater. The results of this study will facilitate understanding of groundwater origin and quality status to enable effective management and utilization of groundwater. Highlights: The integrated methods of hydrochemistry and multiple isotopes are used to identify hydrochemical processes. Salinity (controlled by Na +, Cl − and SO4 2− ) and Fluoride (F − ) are the dominated parameters deteriorating groundwater quality. The rock weathering in conjunction with the cation exchange absolutely predominate the geochemical evolution. SO4 2− is mainly from the dissolution of sulfate minerals and bacterial sulfate reduction is occurred in CJY aquifer. The fluoride of the groundwater is mainly controlled by CaF2 solubility.